Food safety for the 21st century : managing HACCP and food safety throughout the global supply chain - Wallace, Carol A. (Blackwell Pub., 2011)
The HACCP (Hazard Analysis and Critical Control Points) system is still recognised internationally as the most effective way to produce safe food throughout the supply chain, but a HACCP system cannot operate in a vacuum. It requires prerequisite programmes to be in place and it can be highly affected by, or dependent upon, other major considerations such as animal, plant, human and environmental health, food security and food defence. This book: Provides a practical and up-to-date text covering the essentials of food safety management in the global supply chain, giving the reader the knowledg.